Penyusunan Derajat Urbanisasi untuk Perhitungan Indikator Suistainable Development Goals - Wida Widiastuti; Achmad Fauzi Bagus Firmansyah; Novia Permatasari (Seminar Nasional Official Statistics, 2022)
Global methodology for delineating urban-rural areas is needed for monitoring the indicator of Sustainable Development Goals. The degree of urbanization, proposed method by United Nations, can classify cluster area into three-level categories; urban centers, urban clusters, and rural. The classification is calculated considering three aspects; population density, proportion of settlement areas, and neighborhood contiguity. This method can be implemented for calculating the indicator 9.1.1, namely Rural Access Index (RAI). This index reflects the accessibility of rural populations within 2 km radius of all-season roads. The results show significant inequality between two provinces, Nusa Tenggara Barat (NTB) and Nusa Tenggara Timur (NTT). The distribution of NTB’s population is dominated by urban centers (55.6%) and urban clusters (36.39%), whereas the majority of NTT’s population lives in rural areas (44.74%). The RAI results, 23.22% of NTT’s rural population has inadequate access to the all-season roads which is higher than NTB’s rural population (6.46%).